Real Slices of SL(, ℂ)-Opers - Biswas, Indranil; Heller, Sebastian; Schaposnik, Laura P. (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
Through the action of an anti-holomorphic involution (a real structure) on a Riemann surface , we consider the induced actions on SL(, ℂ)-opers and study the real slices fixed by such actions. By constructing this involution for different descriptions of the space of SL(, ℂ)-opers, we can give a natural parametrization of the fixed point locus via differentials on the Riemann surface, which in turn allows us to study their geometric properties.